Use of bauxite waste as filler, added polypropylene from mineral water bottle residue in hot-machined bituminous concrete (Research, Society and Development, 2023)
The present study aims to evaluate the use of bauxite residue, together with polypropylene, from mineral water bottles, in the composition of Hot Mixed Bituminous Concrete - CBUQ. For this purpose, compositions were elaborated with three different percentages of bauxite residue (3%, 5% and 7%), mixtures using only polypropylene, in the contents of (1%, 3% and 5%), and dosages with substitution of 3% filler from bauxite residue and 3%  polypropylene.               The constituent materials were characterized in terms of chemical, physical and microstructural composition. The bauxite residue was evaluated in terms of granulometry, microstructure, pH, specific mass and  chemical composition. The aggregates were submitted to tests of specific mass, abrasion, shape index and adhesiveness and, framed in the theoretical granulometric curve corresponding to the average of “Range C” of DNIT. For the CAP 50/70 binder, the penetration test, softening point and viscosity were carried out. The performance of the  asphalt mixtures was measured using the parameters of the Marshall test and the results of static diametral  compression traction at 25°C minimum MPa. The water from the conditioning at 60°C of specimens consisting of bauxite residue was collected and evaluated for pH and concentrations of iron and aluminum. The results showed that there is a prospect of improving the Marshall parameters for different contents of bauxite residue used as filler and polypropylene, creating alternative materials in the constitution of pavements, capable of conferring satisfactory  mechanical properties to traffic, without contaminating the environment.